Odpowiedzi

Najlepsza Odpowiedź!
2009-11-19T19:58:50+01:00
1. (ab - a) * (2ab + 6a)=2a²b²+6a²b-2a²b-6a²=2a²b²+4a²b-6a²=a²(2b²+4b-6)

2. Zapisz w postaci sumie algebraicznej pole:
Prostokąta o bokach x + 5 i x - 2
a=x+5
b=x-2

P=ab
P=(x+5)(x-2)=x²-2x+5x-10=x²-3x-10
2009-11-19T20:00:24+01:00
(ab - a) * (2ab + 6a)= 2a²b² + 6a²b - 2a²b - 6a²= 2a²b² + 4a²b - 6a²= 2a²(b² + 2b - 3a²)

(x + 5)( x - 2) = x² +2x + 5x - 10= x² +7x -10
2009-11-19T20:07:43+01:00
1
(ab - a) * (2ab + 6a)= 2a²b²-6a²b-2a²b-6a²=2a²b²-4a²b-6a²
2 Pole =a×b=(x + 5) ×( x - 2)
P=(x + 5) ×( x - 2)=x²-2x+5x-10=x²-7x-10